2016
DOI: 10.18781/r.mex.fit.1604-1
|View full text |Cite
|
Sign up to set email alerts
|

Detección de Iris yellow spot virus en cebolla cultivada en Tepalcingo, Morelos, México

Abstract: Detection of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0
6

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 13 publications
0
6
0
6
Order By: Relevance
“…The S segment contains the N gene that encodes for capsid nucleoprotein that is commonly used to identify and classify tospoviruses, because of its degree of divergence , as well as to study geographic distribution and genetic diversity (Iftikhar et al, 2014). IYSV is widely distributed worldwide (Gent et al, 2006) but in Mexico it has been reported since 2012 on onion crops in the state of Morelos, where it causes a disease known as "yellow spot" with 100% incidence and more than 90% severity (Ramírez et al, 2016). In Morelos, two types of symptoms associated with IYSV have been observed and, for this reason, the objective of this research was to describe the symptoms caused by both isolates on Nicotiana benthamiana, and to find out if there are differences in the N segment of the genome and its phylogenetic relation with other isolates.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The S segment contains the N gene that encodes for capsid nucleoprotein that is commonly used to identify and classify tospoviruses, because of its degree of divergence , as well as to study geographic distribution and genetic diversity (Iftikhar et al, 2014). IYSV is widely distributed worldwide (Gent et al, 2006) but in Mexico it has been reported since 2012 on onion crops in the state of Morelos, where it causes a disease known as "yellow spot" with 100% incidence and more than 90% severity (Ramírez et al, 2016). In Morelos, two types of symptoms associated with IYSV have been observed and, for this reason, the objective of this research was to describe the symptoms caused by both isolates on Nicotiana benthamiana, and to find out if there are differences in the N segment of the genome and its phylogenetic relation with other isolates.…”
mentioning
confidence: 99%
“…Onion leaf tissue was classified based on the severity of the symptoms observed, frozen with liquid nitrogen and stored at -80 °C. Nicotiana benthamiana plants were mechanically inoculated (Mandal et al, Fully Bilingual revista Mexicana de FITOPATOLOGÍA Mexican Journal oF PhytoPatholoGy incidencia de 100% y severidad superior al 90% (Ramírez et al, 2016). En esta entidad se han observado dos tipos de síntomas asociados a IYSV por lo que la presente investigación tuvo como objetivo describir los síntomas que ocasionan ambos aislamientos en Nicotiana benthamiana, conocer si hay diferencias en el segmento N del genoma y su relación filogenética con otros aislamientos.…”
unclassified
See 3 more Smart Citations